Oil Yield And Fatty Acid Profile Of Staggered Sown Spring Sunflower (Helianthus Annuus L.) In Response To Foliar Application Of Boron And Tiba (Applied Biological Research, 2017)
Investigations were conducted at PAU, Ludhiana (India) during 2014 and  2015 to assess the effect of foliar application of boron @ 110, 220 and 440  pm and 2,3,6-tri-iodo-benzoic acid (TIBA) @ 100, 200 and 400 ppm on oil  yield and fatty acid profile of staggered sown (January 20, February 10 and  March 2) spring sunflower. Studies revealed that delayed sowing reduced oil  content and yield with concomitant increase in protein content. Increase in  oleic acid with concomitant decrease in palmiticand linoleic acids was also  noted as the sowing was delayed. Foliar application of boron and TIBA did  not influence the oil content and its fatty acid composition but caused  significant improvement in protein content and oil yield. Correlation studies  revealed that oil content, oil yield and linoleic acid were highly significant  (p
Keywords: Linoleic acid; oil content, o; oil content; oleic acid; protein content; sowing date